Bioremediation of low-density polyethylene (PE) by Fungi - Maan Shake, Mariam; Khlaif, Abbas T. (Journal of Neonatal Surgery, 2025)
The necessity of having eco-friendly disposal policies designed for biodegradation of synthetic plastics is of utmost importance and needs attention in the present scenario, considering the serious impact of widely used packaging materials such as low-density polyethylene (PE) on the environment. Our study aimed to explore the degradation of PE by three different fungi species. Alternaria alternata, Aspergillus, Penicillium The extent of biodegradation was evaluated by weight loss of the PE samples. The weight of the plastic sample before degradation was 1 gr and after the degradation, the sample weight of polyethylene (PE) was (0.15%;0.3%8,0.92%,) gr respectively. Scanning electron microscope (SEM) analysis revealed that morphological changes in the surface of PE were observed while FTIR images showed functional groups changes after 90 days incubation period. The formation of biofilms on the surface of polyethylene and the adhesion capabilities of fungi are seen as the first step in the biodegradation process. These results. can colonize, modify and utilize PE as the sole carbon source, water. This manuscript also paves the way for future studies on biodegradation to solve the global problem.